PERAN BUMDES DALAM PENGADAAN INPUT PRODUKSI PERTANIAN DI DESA MAPERAHA KECAMATAN SAWERIGADI KABUPATEN MUNA BARAT - Samlan Samlan; Usman Rianse; Ima Astuty Wunawarsih (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
National development strategies prioritize villages by implementing autonomy policies and fortifying Village-Owned Enterprises (BUMDes) as economic institutions grounded in local potential. These enterprises play a pivotal role in enhancing community welfare, curbing inequality, and fostering village economic autonomy. However, various challenges persist in their management, including budgetary limitations and institutional capacity. The objective of this study is to provide a comprehensive analysis of the role of BUMDes in the procurement of agricultural production inputs in Maperaha Village, Sawerigadi District, West Muna Regency. The number of subjects in this study was 15, selected using purposive sampling. The data were collected through a combination of interviews, observational studies, and documentation techniques. The research variables were the role and factors inhibiting BUMDes in the procurement of agricultural production inputs. The data analysis method employed in this study was descriptive analysis. The results indicated that the role of the Village-Owned Enterprise (BUMDes) of Maperaha Village in the procurement of agricultural production inputs, including seeds, fertilizers, agricultural tools, and pesticides, was still low and not yet optimal. The procurement of production inputs has not yet been fully aligned with the needs of farmers, nor has it been distributed equally among the community. The condition is influenced by several factors, including limited facilities and infrastructure, low community participation, and a weak human resource capacity among BUMDes managers and management.